The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1678-457x.20616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time and storage conditions on the physical and physico-chemical characteristics of the pulp of yellow and purple passion fruit

Abstract: The aim of this study was evaluate the physical and physico-chemical characteristics of extracted fruit pulp of passion fruit with different skin color (yellow, light and dark purple) under refrigeration temperatures and storage times. The extracted pulp of passion fruit was stored at different temperatures: 10 °C, 25 °C; -30 °C and -80 °C and at four different storage periods: 0; 10; 20 and 30 days. The following physical and physico-chemical characteristics of the fruit were evaluated: color of fruit peel, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…The decrease in the pH value relates to TA and consumption of organic acids during ripening, when these acids act as substrates in the respiratory process (SILVA et al, 2005). However, increase in these values may occur in some fruits along storage, as can be observed in yellow passion fruits (2.74-2.80) (ARAÚJO et al, 2017).…”
Section: Frutos De Ora-pro-nóbis (Pereskia Aculeata Miller) Maduros Ementioning
confidence: 99%
“…The decrease in the pH value relates to TA and consumption of organic acids during ripening, when these acids act as substrates in the respiratory process (SILVA et al, 2005). However, increase in these values may occur in some fruits along storage, as can be observed in yellow passion fruits (2.74-2.80) (ARAÚJO et al, 2017).…”
Section: Frutos De Ora-pro-nóbis (Pereskia Aculeata Miller) Maduros Ementioning
confidence: 99%
“…Média ± 1 erro padrão Intervalo dentro 1,5IQR Mediana Média Amostras A seriguela apresentou-se como a fruta mais ácida, exibindo um valor de pH 1,89. Esse caráter ácido explica um grande fator delimitante na predisposição para o desenvolvimento de bactérias, tanto nas frutas como nos próprios alimentos em geral, além de ajuda na colaboração para sua conservação (ARAÚJO et al, 2017). Por integrarem a mesma espécie do cajá (Spondias), foi possível comparar seus resultados entre si, que visto que os padrões de identidade e qualidade de pH para polpa de cajá por exemplo, deve ser de no mínimo 2,2 evidenciando assim valores distintos entre seriguela e cajá.…”
Section: Ph E Acidez Total Titulávelunclassified
“…Passion fruit ( Passiflora edulia Sims) is an important tropical and subtropical species with high commercial value due to its attractive flavor and aroma and nutrients with beneficial properties for human health, such as vitamins C, B1 and B2 and essential amino acids, as well as various minerals and fibers [ 1 , 2 ]. This species can be planted and grown in many regions and is in high demand in the market for fresh fruit and processed foods and juices [ 3 ]. Passion fruit has been reported to have high contents of phytochemicals with antioxidant, anti-inflammatory and anticancer properties, which are associated with a lower risk of cardiovascular diseases, cancer and metabolic diseases [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of studies have reported the postharvest conservation of various fresh fruits. The method of applying chemical or physical preservatives is widely employed to conserve fresh fruit because this method is the simplest and least expensive [ 3 ]. For climacteric fruit, the ethylene production rate usually increases rapidly during storage, which may accelerate the process of fruit softening or lead to physiological disorders [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation